Fibrosis mechanism, crystallization behavior and mechanical properties of in-situ fibrillary PTFE reinforced PP composites. (1st December 2021) - Zhang, Aimin; Chai, Jialong; Yang, Chunxia; Zhao, Jinchuan; Zhao, Guoqun; Wang, Guilong
Graphical abstract: Highlights: An approach to control morphology of PTFE in PP was proposed. Fibrosis mechanism of PP/PTFE microfibril reinforced composites was elucidated. Crystallization of PP/PTFE composites with different morphology was studied. PP/PTFE microfibril reinforced composites showed superior mechanical properties. Abstract: In-situ fibrillary PTFE was usually developed by melt blending to enhance the melt strength and processability of PP. However, the fibrosis mechanism and the morphology evolution of PTFE during in-situ fibrillation process is still unclear. In this study, both in-situ PP/fibril-PTFE and PP/spherical-PTFE composites were prepared by one-step extrusion process. DSC, XRD, SEM, AFM, as well as O-PTIR analysis were conducted to elucidate the fibrosis mechanism of PTFE. The main reason for the in-situ fibrillation of PTFE-3800 could be ascribed to the chain-extended crystal structure. Furthermore, the acrylate layer of PTFE-3800 can also help PTFE to develop into fibrils. Shear rate was the key parameter in affecting the morphology evolution of PTFE, while processing time could also affect the morphology of PTFE to a certain extent. Interestingly, the SEM analysis showed that reticular crystals are generated in the presence of PTFE fibrils, while spherulites were generated in the presence of PTFE particles. Simultaneous enhancements in the strength, modulus and rigidity were achieved for in-situ fibrillary PTFE reinforced PP composites.